2020
DOI: 10.1080/15389588.2020.1841179
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the scalp on the effectiveness of bicycle helmets' anti-rotational acceleration technologies

Abstract: Objective: Medical data has lead to the common understanding that bicycle helmets need to be improved to better protect against brain injuries resulting from rotational acceleration. Although many different technologies exist for reducing rotational acceleration during impacts, the lack of an official testing standard means that their evaluation is based on customised set-ups that may differ and not represent real accident conditions. Previously, the authors have shown that scalp tissue plays an important role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…The difference between the response of headforms under the same oblique impact conditions and using the same helmet can stem from the large difference in the coefficient of friction (CoF) at the headform/liner interface. Previous studies have shown that this CoF has significant effects on the head kinematics during oblique impact (Trotta et al, 2018b;Zouzias et al, 2021). Human skin at different regions has very different surface frictions, depending on the skin surface condition and hydration (Derler et al, 2015).…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…The difference between the response of headforms under the same oblique impact conditions and using the same helmet can stem from the large difference in the coefficient of friction (CoF) at the headform/liner interface. Previous studies have shown that this CoF has significant effects on the head kinematics during oblique impact (Trotta et al, 2018b;Zouzias et al, 2021). Human skin at different regions has very different surface frictions, depending on the skin surface condition and hydration (Derler et al, 2015).…”
Section: Discussionmentioning
confidence: 98%
“…In contrast to this headform, the MoIs and CoF of the Cellbond headform are in better agreement with those obtained from measurements on live and postmortem human subjects ( Trotta et al, 2018a ; Connor et al, 2020 ). Previous research has studied helmet response with headforms that have more biofidelic MoIs ( Kendall et al, 2012 ; Connor et al, 2020 ) or CoF ( Trotta et al, 2018b ; Juste-Lorente et al, 2021 ; Zouzias et al, 2021 ) but not a headform that has both. For the first time, this study used a headform that has both biofidelic CoF and MoIs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations